Valgus slipped capital femoral epiphysis: presentation, treatment, and clinical outcomes using patient-reported measurements. Issue 2 (13th April 2020) - Gelink, Andrés; Cúneo, Alejandro; Silveri, Claudio; Tiderius, Carl J.; Loder, Randall; von Heideken, Johan
Abstract : Valgus slipped capital femoral epiphysis (SCFE), is rare. This study describes the diagnosis, treatment and outcome of valgus SCFE in Uruguay. The medical records and radiographs were reviewed in eight consecutive children [mean age 11.9 years (range 9–13; six female)] with valgus SCFE between 1997–2017. In 2018–2019, all patients were reexamined clinically, new radiographs obtained, and patient-reported outcomes completed using the international tool of hip results (iHOT-12). The prevalence of clinical femoroacetabular impingement (FAI), avascular necrosis, and surgical complications were also studied. There were 11 valgus SCFEs in eight patients; two had primary bilateral SCFEs, and one child later developed a valgus SCFE in the contralateral hip. Seven out of eight patients were overweight. All were stable idiopathic SCFEs. The mean femoral head shaft angle on the anteroposterior radiographs for the 11 SCFEs was 145° (range 140–168) and 141° (range 139–145) for the six healthy contralateral hips. Slip severity measured on the Lauenstein projection was mild (<30°) in eight hips and moderate (30°–60°) in three hips. At a mean follow-up of 87 months (range 24–252), there were no cases of avascular necrosis. The mean iHOT12 was 74 (range 13–97). Significant remodeling was detected in both head shaft angle (8°) and alpha angle (10°) in the affected hips. Nine hips (81%) demonstrated clinical signs of FAI. Our study is the first to describe long-term results using both clinical and patient outcome measures (iHOT-12). A majority of patients have residual symptoms, likely associated with FAI.